PENGARUH HARGA, KUALITAS PRODUK DAN GAYA HIDUP TERHADAP WILLINGNESS TO PAY (WTP) SEMANGKA ORGANIK - Lydia Indra Setung; Yoseph Yakob Da Rato (Program Studi Agribisnis, Fakultas Pertanian, 2021)
People's food consumption patterns are increasingly shifting towards healthy lifestyle changes. The emergence of awareness of the dangers of chemical substances makes people more selective in choosing a product for their consumption. one food alternative that refers to a healthy lifestyle is organic watermelon. The price of organic watermelon is relatively expensive to create its own attraction for consumers of a certain class. This study aims to find out the influence of product prices, product quality, and lifestyle on willingness to pay (WTP) organic watermelon. The data analysis used is descriptive analysis, and Multiple Linear Regression Analysis. The research was conducted in the Practice Garden of the Faculty of Agriculture, University of Nusa NipaIndonesia for 2 months from 01 October – 04 December 2020. Sampling techniques using Accidental Sampling with the number of respondents as many as 38 people. The results showed lifestyle variables had a partially significant effect on willingness to pay organic watermelon. Meanwhile, all variables (Product price, Product Quality, and Lifestyle) have a significant effect simultaneously (together) on willingness to pay organically in the Garden of the Faculty of Agriculture, University of Nusa Nipa Indonesia.